Pemanfaatan Media Pembelajaran Sebagai Sarana Ujian Berbasis Daring - Dito Putro Utomo; Bister Purba (Jurnal ABDIMAS Budi Darma, 2021)
In order to improve the quality and quality of learning in educational institutions, technological developments are needed in achieving that goal. Especially during the Corona Virus Disease 2019 (COVID-19) pandemic, which requires teaching and learning activities to be carried out online. SMP IT Al-Munadi, which is an educational institution under the auspices of the Al-Munadi Waqf Foundation, tries to take advantage of technological developments so that the learning process takes place effectively, especially in the implementation of exams. Manual exams were not allowed during the Corona Virus Disease 2019 (COVID-19) pandemic. In addition, manual exams have many obstacles such as the possibility of cheating by students when answering exams and requiring additional time for teaching staff to check student exam results. The use of instructional media is an alternative to these problems, where using a learning media application can change the exam process manually to online. Therefore, the community service carried out by the team is conducting training on the use of learning media as a means of online examinations.Keywords: Usage, Media, Learning, Exam, Online